Climate smart agriculture technologies adoption among small-scale farmers: a case study from Gujarat, India - Hebsale Mallappa, Vinaya Kumar; Pathak, Tapan Bharatkumar (Frontiers in Sustainable Food Systems, 2023)
In India, 78% of farmers are small and marginal, cultivating only 33% of the arable land but producing 50% of the food grain; their vulnerability to climate change poses a significant threat to the country’s food security. To enhance agricultural resilience, it is crucial to understand how these farmers perceive and integrate climate-smart technologies into their farming practices. A random sample of 240 farmers was selected for this study. An ex-post facto research design was employed to investigate farmers’ awareness of and adoption of CSAT and identify the significant variables influencing their decisions. The results indicate that approximately 74 per cent of farmers had low to medium awareness of CSAT, while around 83 per cent had low to medium adoption rates. Several factors were found to be significantly correlated with farmers’ awareness and adoption of CSAT, including education level, annual income, exposure to agricultural mass media, participation in extension programs, innovativeness, achievement motivation, risk orientation, and scientific orientation. Additionally, farmers faced various challenges in adopting CSAT, such as the high cost of inputs, limited knowledge about CSAT, and youth migration from rural areas. Based on the study’s findings, farmers emphasized the importance of involving them in decision-making processes related to the development of climate-smart technologies. They also highlighted the need for a timely supply of inputs and field visits to successful farms as effective means to promote awareness and adoption of CSAT. The comprehensive analysis of associated factors and empirical findings presented in this study will benefit private sector organizations, government extension agents, academics, and policymakers. By gaining insights into the determinants of CSAT adoption, these stakeholders can focus their efforts more effectively on promoting widespread adoption. Additionally, this study can inform policy decisions regarding the allocation of government resources to combat climate change.